Avaliação de fungos entomopatogênicos visando ao controle da ampola da erva-mate Gyropsylla spegazziniana (Lizer & Trelles) (Hemiptera: Psyllidae) - Formentini, Marina Andressa (2012)
This study aimed to select and characterize strains of entomopathogenic fungi in order to control Gyropsylla spegazziniana. For this, the fifth instar nymphs were transferred to Paraguay tea seedlings, followed by spraying conidial suspensions of 48 strains of Beauveria spp., Metarhizium anisopliae, Isaria spp. and Lecanicillium spp. at a concentration of 1 × 109 conidia/mL. The seedlings were placed in PVC cages kept in a climatized room (26 ± 1°C; 12 h photophase and 60 ± 10% R.H.), and the insect mortality was evaluated daily for 10 days. The most active isolates were compared by means of vegetative growth, conidial production in culture media, insecticidal activity and molecular analyses, by sequencing the region rDNA-ITS and RAPD. The genus 22 Beauveria spp. was more efficient among the entomopathogenic fungi, especially for strain Unioeste 44 that showed the best performance, demonstrating its potential to control the pest. Molecular analysis of rDNA-ITS region allowed the identification of isolates as B. bassiana e B. brongniartii and RAPD markes were associated with virulence